Diabetes mellitus and renal failure effect on intestinal insulin - Asrar Ali; Noor-Alhooda M Al-Awkally; Areeb Ahmer; Sania Tariq; Talha Mumtaz; Huma Shahbaz; Rabbya Rayan Shah (ITScience (Information Technology and Science), 2022)
The two most prevalent causes of end-stage renal disease nowadays are thought to be diabetic mellitus (DM) and hypertension (ESRD). In addition to discussing the function of DM in ESRD, this study reviews glucose metabolism and the treatment of hyperglycemia in these patients. Although strict glycemic control and ESRD patient survival were not significantly correlated in numerous big trials, it is advised that glycemic control be prioritised as the primary therapeutic objective in the care of these patients to minimise harm to other organs. When fasting blood sugar is less than 140 mg/dL, 1-hour postprandial blood sugar is less than 200 mg/dL, and glycosylated haemoglobin (HbA1c) is 6-7 in type 1 diabetes patients and 7-8 in type 2 diabetes patients, glycemic control is ideal. Given its potentially deadly side effect, lactic acidosis, metformin administration should be avoided in patients with chronic renal failure (CRF), while glipizide and repaglinide seem to be preferable options.